Femtoseconds soliton mode-locked erbium-doped fiber laser based on nickel oxide nanoparticle saturable absorber - Nady, A.; Ahmed, Mahmoud Hazzaa M.; Latiff, Anas Abdul; Raymond Ooi, C.H.; Harun, Sulaiman Wadi (Optical Society of America, 2017)
We demonstrate a femtosecond mode-locked erbium-doped fiber laser (EDFL) using a nickel oxide (NiO) as a saturable absorber (SA). NiO nanoparticles are hosted into polyethylene oxide film and attached to fiber ferrule in the laser cavity. The NiO-SA shows a 39% modulation depth with a 0.04 MW/cm2 saturation intensity. Our ring laser cavity based on erbium-doped active fiber with managed intracavity dispersion has the ability to generate ultrashort pulses with a full width at half-maximum (FWHM) of around 2.85 nm centered at 1561.8 nm. The pulses repeat at a frequency of 0.96 MHz and duration of 950 fs.